Photoelectron Properties and Organic Molecules Photodegradation Activity of Titania Nanotubes with CuxO Nanoparticles Heat Treated in Air and Argon - Elizaveta Konstantinova; Timofey Savchuk; Olga Pinchuk; Ekaterina Kytina; Elizaveta Ivanova; Lidiya Volkova; Vladimir Zaitsev; Alexander Pavlikov; Elena Elizarova (Molecules, 2022)
Titania is very famous photocatalyst for decomposition of organic pollutants. Its photocatalytic properties significantly depend on the morphology and chemical composition of the samples. Herein, the TiO2 nanotubes/CuxO nanoheterostructures have been synthesized and the effect of heat treatment performed in molecular atmospheres of air and argon on their photoelectrochemical and photocatalytic properties has been studied. The prepared samples have a higher reaction rate constant compared to TiO2 nanotubes in the decomposition reaction of methylene blue molecules. It is established that in argon treated nanoheterostructures, the copper oxide is present in two phases, CuO and Cu2O, while in air treated ones there is only CuO. In the TiO2 nanotubes/CuxO samples, Cu2+ ions and molecular O2− radicals were detected while in TiO2 nanotubes only carbon dangling bond defects are present. The dynamics of O2− radicals under illumination are discussed. It was shown that the TiO2 nanotubes do not exhibit photocatalytic activity under visible light. The mechanism of the photocatalytic reaction on the surface of the TiO2 nanotubes/CuxO samples was proposed. It is assumed that a photocatalytic decomposition of organic molecules under visible light at the surface of the nanoheterostructures under investigation is realized mainly by the reaction of these molecules with photogenerated O2− radicals. The results obtained are completely original and indicate the high promise of the prepared photocatalysts.